Diversity of endophytic bacteria in rubber roots and its potential against white root disease (Rigidoporus lignosusi) / Mohd Fiqri Bahari - Bahari, Mohd Fiqri (Faculty of Plantation and Agrotechnology, 2014)
Endophytic bacteria have been isolated from roots of Hevea briensiliensis with three difference types which are mature and immature commercial type s and immature of wild types. All the samples were taken from Tanah Wakaf area Nyalas, Melaka and the clone taken for the commercial types was RRIM 2025. Fourteen endophytic bacteria were successfully isolated from the roots samples. These isolated endophytic bacteria were tested for its antagonism activity against Rigidoporus lignosus pathogen a causal of white roots disease of rubber by using a dual culture test. These isolated were also tested for preproduction of secondary metabolites that have potential to inhibit the growth of the pathogen through a culture filtrate test. Two isolated named as EBI and EB4 showed the highest percentage of inhibition radial growth (PIRG) of R. lignosus with the values of 72.94% and 68% respectively on dual culture test. Meanwhile the isolated of EB1 and EB4 bacteria produce secondary metabolites that could inhibit the pathogen growth with 57.69% of PIRG and 69.41%l respectively.